On Sustaining Dynamic Adaptation of Context-Aware Services - Boudjemaa Boudaa; Slimane Hammoudi; Abdelkader Bouguessa; Leila Amel Mebarki; Mohammed Amine Chikh (EAI Endorsed Transactions on Context-aware Systems and Applications, 2015)
The modern human is getting more and more mobile having access to online services by using mobile cutting-edge computational devices. In the last decade, the field of context-aware services had led to emerge several works. However, most of the proposed approaches have not provided clear adaptation strategies in case of unforeseen contexts. Dealing with this last at runtime is also another crucial need that has been ignored in their proposals. This paper aims to propose a generic dynamic adaptation process as a phase in a model-driven development life-cycle for context-aware services using the MAPE-K control loop to meet the runtime adaptation. This process is validated by implementing an illustrative application on FraSCAti platform. The main benefit of the proposed process is to sustain the self-reconfiguration of such services at model and code levels by enabling successive dynamic adaptations depending on the changing context.